On Approximately p-Wright Affine Functions in Ultrametric Spaces. (28th October 2013) - Bahyrycz, Anna; Brzdęk, Janusz; Piszczek, Magdalena
Abstract : We prove some results for mappings taking values in ultrametric spaces and satisfying approximately a generalization of the equation of p -Wright affine functions. They are motivated by the notion of stability for functional equations.